2018
DOI: 10.4103/ijciis.ijciis_4_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of opioids as coinduction agent with propofol and their effect on apnea time, recovery time, and sedation score

Abstract: Background:Laryngeal mask airway (LMA) is a supraglottic device which requires lesser depth of anaesthesia, evokes lesser hemodynamic response and causes lesser stimulation of airway as compared to traditional definitive airway device endotracheal tube. Its placement is possible without muscle relaxants thereby allowing maintenance of anaesthesia on spontaneous respiration thus preventing apnoea or minimizing apnoea time. Propofol, the commonly used induction agent, causes cardiorespiratory depression at highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
4
1
Order By: Relevance
“…Taking together, we used fentanyl and sevoflurane for modifying depth of anesthesia to attenuate cough and the result was consistent with previous studies reporting that depth of anesthesia can modify cough reflex. [ 30 32 ] However, there was no significant difference in BIS value between 2 groups before OLV and during surgery in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Taking together, we used fentanyl and sevoflurane for modifying depth of anesthesia to attenuate cough and the result was consistent with previous studies reporting that depth of anesthesia can modify cough reflex. [ 30 32 ] However, there was no significant difference in BIS value between 2 groups before OLV and during surgery in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…During anesthesia our patients were administered the drugs characterized by an expressed vagotonic and sympathoplegic effect, what became the priory of the maximum number of respiratory complications. [ 17 18 19 20 ] The conducted study showed that pain was a unique significant postoperative complication, which was proved by the studies of other scientists. [ 21 22 23 ]…”
Section: Discussionmentioning
confidence: 97%
“…They are inexpensive when patient safely discharged early. This analysis aimed to discover a cost-effective induction drug, an alternative to propofol that is preferred drug but quite costly in day-cases surgeries [15][16] . Concomitant 0.25 mg / kg oral midazolam induction and conventional intravenous thiopental at a compact dosage of 2.5 mg / kg resulted in recovery almost similar to that of propofol [17][18] .…”
Section: Discussionmentioning
confidence: 99%